2009
DOI: 10.1088/1367-2630/11/10/103014
|View full text |Cite
|
Sign up to set email alerts
|

Negative compressibility of selenium chains confined in the channels of AlPO4-5 single crystals

Abstract: Pressure induced structural and electronic transitions of Se helical chains confined inside nano-channels are studied. Raman scattering and optical absorption experiments show strong evidence of band gap reduction under high pressure. Ab initio calculations reveal that under hydrostatic compression, the Se chains should elongate and the change in morphology leads to a softening of phonons and narrowing of band gaps, and these signatures are observed in experiments. Our investigation demonstrates a negative com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The crystal structure and mechanical properties of silver oxalate were determined using first principles solid‐state methods. The description of solid‐state crystalline compounds using computational modelling techniques is sufficiently advanced nowadays to predict their mechanical properties in good agreement with experimental measurements . The present computations were carried out separately with several different sets of calculation parameters associated to increasingly more demanding computations and the analysis of the convergence of the calculated crystal structures, associated energies, and properties showed that they were nearly converged with respect to the calculation parameters.…”
Section: Computed Mechanical Properties Of Silver Oxalate In the Reusmentioning
confidence: 98%
“…The crystal structure and mechanical properties of silver oxalate were determined using first principles solid‐state methods. The description of solid‐state crystalline compounds using computational modelling techniques is sufficiently advanced nowadays to predict their mechanical properties in good agreement with experimental measurements . The present computations were carried out separately with several different sets of calculation parameters associated to increasingly more demanding computations and the analysis of the convergence of the calculated crystal structures, associated energies, and properties showed that they were nearly converged with respect to the calculation parameters.…”
Section: Computed Mechanical Properties Of Silver Oxalate In the Reusmentioning
confidence: 98%
“…Negative linear compressibility (NLC) is the anomalous property of expanding in one direction when a compressive hydrostatic pressure is applied. A few materials have been reported in literature to exhibit NLC . It has also been predicted by means of DFT simulations or ab initio calculations in platinum sulfide , some zeolites and metal‐organic frameworks (MOFs) .…”
Section: Introductionmentioning
confidence: 98%
“…Recently, substances with negative isothermal compressibility β were discovered [11][12][13][14][15][16][17]. For them, from Eqs.…”
Section: Resultsmentioning
confidence: 99%